Peranan Kompetensi SDM UMKM Dalam Meningkatkan Kinerja UMKM Crepes di Daerah Kosambi - Evha Khoirunnisa; Dwi Epty Hidayaty; Aulia Ramadhani (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
MSMEs are able to support our country's economy. Because most of the business actors are MSMEs and are able to absorb labor. The Kosambi area is one of the areas in the Karawang district which is used as a fairly dense MSME economic area in the city of Karawang. One of these MSME areas is Duren village as one of the villages that has business potential that can support the economy of the surrounding residents. This study aims to determine the role of MSME HR competencies in improving the performance of MSME Crepes in the Kosambi area. The competence of Human Resources (HR) turns out to be one very important factor in the MSME Crepes industry. By increasing the competence of human resources through increasing knowledge and skills, this is the key to increasing the work of MSME Crepes. UMKM Crepes costs from Rp. 2,500 to Rp. 5,000 are marketed offline by using carts and online through several applications. The turnover obtained from this crepes business is Rp. 180,000 to Rp. 200,000 so per month it can reach Rp. 3,000,000 and return on investment within 3-4 months.